The Effectiveness of Group Counseling Services in Enhancing Social Support for Wives of Drug Offenders in Correctional Facilities - Zakki, Ahmad; Nirwana, Herman; Hariko, Rezki (Department of Guidance and Counseling, FIP, Undiksha, 2024)
The issue faced by the wives of drug offenders is the low level of social support, which can affect their psychological well-being. Therefore, this study aims to examine the effectiveness of group counseling services in enhancing social support for the wives of drug offenders in correctional facilities. This research uses a quantitative approach with a quasi-experimental method and a time-series design (O1-O4 pretest and O5-O8 posttest) to measure changes in the level of social support. The subjects of the study were 10 wives of drug offenders. The research instrument was a social support checklist developed using the Likert scale model. Data collection was carried out by administering the instrument during the pretest and posttest, while data analysis was conducted using N-Gain and Wilcoxon tests. The results of the study indicate that group counseling services were moderately effective in increasing social support, with a positive N-Gain value. Furthermore, the Wilcoxon test showed a Z value of -2.805b and Asymp. Sig. (2-tailed) of 0.005, which indicates that the alternative hypothesis is accepted. Based on these results, it can be concluded that the implementation of group counseling services is effective in increasing social support for the wives of drug offenders.